An evidence-based review of overuse wrist injuries in athletes - Phillips, S. G. (Orthopedic Clinic, 2020)
Overuse injuries are a common source of wrist pain in athletes of all competitive levels. Overuse wrist injuries may result in tendinopathies or osteoarticular issues, such as impactionsyndromes, impingement syndromes, and physeal stress injuries. Most of these conditions can be treated successfully with conservative measures, such as activitymodification, immobilization or bracing, anti-inflammatory medications, therapy, andcorticosteroid injections. Published evidence supports favorable outcomes after treatment of overuse injuries, even ifsurgical intervention is required.